Experimental investigation of hydrogen peroxide RF plasmas. (27th January 2016) - Barni, R; Decina, A; Zanini, S; D'Orazio, A; Riccardi, C
Abstract: This work reports a detailed experimental study of the plasma properties in low pressure RF discharges in hydrogen peroxide and a comparison with argon under the same operating conditions. H2 O2 plasmas have been proposed for sterilization purposes. Electrical properties of the discharge were shown to be similar, as for the RF and DC voltages of the driving electrode. Bulk plasma volume remains stable, concentrated in an almost cylindrical region between the two facing electrodes. It was found that the electron temperature is almost uniform across the plasma and independent of the power level. This is higher than in argon discharges: T e   =  4.6  ±  0.9 eV versus T e   =  3.3  ±  1.1 eV. The plasma density increases almost linearly with the power level and a substantial negative ion component has been ruled out in hydrogen peroxide. Dissociation in the plasma gas phase was revealed by atomic hydrogen and hydroxyl radical emission in the discharge spectra. Emission from hydroxyl and atomic oxygen demonstrates that oxidizing radicals are produced by hydrogen peroxide discharges, revealing its usefulness for plasma processing other than sterilization, for instance to increase polymer film surface energy. On the other hand, argon could be considered as a candidate for the sterilization purposes due to the intense production of UV radiation.